Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key - Swanson, Daniel R. (Zootaxa, 2017)
The genera of Salyavatinae are briefly discussed. Nudiscutella frontispina Murugan & Livingstone, 1990 is considered a junior synonym of Paralisarda malabarica Miller, 1957 syn. nov. Thirteen species are transferred from Petalocheirus Palisot de Beauvois, 1805 and the following new combinations are proposed: Alvilla gulosa (Miller, 1940) comb. nov.; Alvilla obesa (Miller, 1940) comb. nov.; Alvilla spinosissima (Distant, 1903) comb. nov.; Alvilla tyrannus (Miller, 1940) comb. nov.; Platychiria congolensis (Miller, 1950) comb. nov.; Platychiria lapidaria (Miller, 1950) comb. nov.; Platychiria montana (Miller, 1950) comb. nov.; Platychiria praecox (Miller, 1950) comb. nov.; Platychiria similis (Miller, 1950) comb. nov.; Platychiria striata (Miller, 1950) comb. nov.; Platychiria ugandensis (Miller, 1950) comb. nov.; Platychiria unicolor (Miller, 1950) comb. nov.; and Rhachicephala fasciata (Distant, 1903) comb. nov.. Petalocheirus singularis Walker, 1873 is resurrected from synonymy under Petalocheirus malayus Stål, 1859 and transferred to Rhachicephala Truong, Zhao & Cai, 2007, resulting in Rhachicephala singularis (Walker, 1873) stat. rev. et comb. nov. A supplementary description of the female of Valentia langkawiensis Miller, 1940 is included. An updated key to the world genera of Salyavatinae concludes the study.